Quantification of potential groundwater recharge from recharge pond in small watershed - ALI, SHAKIR; GHOSH, N C; SINGH, RANVIR (The Indian Journal of Agricultural Sciences, 2012)
A study was conducted during 2006–08 to estimate the potential groundwater recharge from the recharge ponds in a small watershed of the semi-arid region of Rajasthan. A recharge pond having storage capacity of 0.65 ha m was constructed to harvest the surface runoffs otherwise going the waste from the watershed. The analysis has revealed that the potential recharge rates from the selected recharge pond varied between 0.019 and 0.051 m/day with a mean of 0.024 m/day during the study period. The components of water balance of the pond have been estimated to be, 77% of the stored water as the groundwater recharge to the aquifer underneath the pond, 9% as loss due to water surface evaporation, 13% as the surplus flow from the pond, and 1% as the dead storage in the pond. An exponential recharge regression model depicting relation between daily recharge rate and recharge period has also derived for the study area. This area specific derived relationship will help for determining potential recharge rate for any recharge period